Biofilm Formation and Associated Genes in Listeria Monocytogenes - Warke, S. R.; Ingle, V. C.; Kurkure, N. V.; Tembhurne, P. A.; Prasad, Minakshi; Chaudhari, S.P.; Barbuddhe , S. B. (Indian Journal of Veterinary Sciences and Biotechnology, 2017)
Listeria monocytogenes, an opportunistic food borne pathogen can cause serious infections in immunocompromised individuals. L. monocytogenes is capable of producing biofilm on the surface of food processing lines and instruments.The biofilm transfers contamination to food products and impose risk to public health. In the present study biofilm producing ability of L. monocytogenes isolates were investigated phenotypically and genotypically by microtiter assay and multiplex PCR, respectively. Out of 38 L. monocytogenes isolates 14 were recovered from animal clinical cases, 12 bovine environment and 12 from milk samples. A total of 3 (21.42%) clinical, 2 (16.66%) environment and 3 (25%) milk samples respectively, revealed biofilm production in microtiter assay. Cumulative results showed that 23 (60.52%) out of 38 strains of L. monocytogenes were positive for luxS and flaA gene and 1 (2.63%) was positive only for the flaA gene.